PENGARUH PEMBERIAN PENDIDIKAN MANAJEMEN LAKTASI TERHADAP PERILAKU KETUA DASAWISMA DALAM PENDAMPINGAN IBU MENYUSUI DI KELURAHAN PEDURUNGAN KIDUL KOTA SEMARANG TAHUN 2017 - Ifa Nurchumaida; Sri Achadi Nugraheni; M. Zen Rahfiluddin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
ABSTRACTThe mother’s lack of knowledge about lactation management can result in the low coverage of exclusive breastfeeding. Education on lactation management can involve the dawis chief. During this time the involvement head of dawis in encouraging exclusive breastfeeding is still lacking. Through lactation management can improve the mother's success in breastfeeding. The purpose of this study was to determine the effect of lactation management education by using booklet as the media on the knowledge, behavior and practice of the Dasawisma head in breastfeeding assistance in Pedurungan Kidul Sub-District.This was a pre-experimental study with one group pretest-posttest design. The sample used in this study was 37 head of dawis who has breastfeeding mothers of less than six months in their area. After that, the sample was analyzed by using wilcoxon signed ranks test. The average knowledge was increased 4,81 (p=0.0001). Increased knowledge about giving water to the baby, the breastfeeding position, bonding, how to make the baby burp and to properly store the breast milk. The average behavior was increased 1,08 (p=0.0001) to the dawis head’s behavior in bonding with the baby while breastfeeding, stimulating the baby to open their mouth before being breastfed, as well as on how to breastfeed and give breast milk properly. The average practice was increased 4,19; this meant there was also an effect of the booklet (p=0.0001) in the pratice. The dawis head’s practice was improved. The head of dawis understood about breastfeeding position, the importance of hygiene before breastfeeding, bonding, burping the baby, how to breastfeed and give the milk, and oxytocin massage. It can be concluded that the booklet can influence the knowledge, behavior and practice of the dasawisma head regarding the lactation management in breastfeeding assistance. It is suggested that to improve the knowledge, behavior and practice on lactation management can be doneby using attractive or interesting media.